Respuesta :

Answer: 2, -1

Step-by-step explanation:

We can substitute y = -2x+3 from the first equation into the second equation.

This results in 4x - 3(-2x+3) =11

We distribute the negative 3 to get 4x + 6x - 9=11

By grouping like terms we get 10x-9=11

Add the 9 to both sides to cancel it out on the left and we get 10x = 20.

This means that x = 2. Now we can substitute x into the original equation. I will use the top one. y=-2(2)+3 is equal to -1, therefore the solution is (2, -1'.

Answer:

(2,-1)

Step-by-step explanation:

x= 2 y= -1

ACCESS MORE